Endodermal apoplastic barriers are linked to osmotic tolerance in meso-xerophytic grass Elymus sibiricus - Liu, Xin; Wang, Ping; An, Yongping; Wang, Chun-Mei; Hao, Yanbo; Zhou, Yue; Zhou, Qingping; Wang, Pei (Frontiers in Plant Science, 2022)
Drought is the most serious adversity faced by agriculture and animal husbandry industries. One strategy that plants use to adapt to water deficits is modifying the root growth and architecture. Root endodermis has cell walls reinforced with apoplastic barriers formed by the Casparian strip (CS) and suberin lamellae (SL) deposits, regulates radial nutrient transport and protects the vascular cylinder from abiotic threats. Elymus sibiricus is an economically important meso-xerophytic forage grass, characterized by high nutritional quality and strong environmental adaptability. The purpose of this study was to evaluate the drought tolerance of E. sibiricus genotypes and investigate the root structural adaptation mechanism of drought-tolerant genotypes’ responding to drought. Specifically, a drought tolerant (DT) and drought sensitive genotype (DS) were screened out from 52 E. sibiricus genotypes. DT showed less apoplastic bypass flow of water and solutes than DS under control conditions, as determined with a hydraulic conductivity measurement system and an apoplastic fluorescent tracer, specifically PTS (trisodium-8-hydroxy-1,3,6-pyrenetrisulphonic acid). In addition, DT accumulated less Na, Mg, Mn, and Zn and more Ni, Cu, and Al than DS, regardless of osmotic stress. Further study showed more suberin deposition in DT than in DS, which could be induced by osmotic stress in both. Accordingly, the CS and SL were deposited closer to the root tip in DT than in DS. However, osmotic stress induced their deposition closer to the root tips in DS, while likely increasing the thickness of the CS and SL in DT. The stronger and earlier formation of endodermal barriers may determine the radial transport pathways of water and solutes, and contribute to balance growth and drought response in E. sibiricus. These results could help us better understand how altered endodermal apoplastic barriers in roots regulate water and mineral nutrient transport in plants that have adapted to drought environments. Moreover, the current findings will aid in improving future breeding programs to develop drought-tolerant grass or crop cultivars.